Intersex Legal activism. United Nations on the Human Rights of Intersex People - Winter Pereira, Luisa (The Age of Human Rights Journal, 2022)
For some years now, two intersex associations, Brújula Intersex and Stop Intersex Genital Mutilation, have been coordinating the participation in evaluation processes of the rights of intersex people convened by the United Nations. This article will try to analyse the legal strategies of these two associations to obtain the condemnation of several states by the United Nations. The ultimate goal is to draw a common thread of life stories, functioning of medical devices, silencing by governmental authorities, and possibilities for intersex people’s agency.